2021
DOI: 10.1590/1980-0037.2021v23e78769
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial development and mental health in youth Brazilian club athletes: examining the effects of age, sport type, and training experience

Abstract: Physical activity occurring through organized sport has been positioned as an engaging manner not only to prevent chronic-degenerative diseases but also to promote healthier societies. However, there is a lack of evidence linking competitive sport participation in the club environment in promoting youth athletes’ psychosocial development and mental health. Thus, this study aimed to analyze the effects of age, sport type, and training experience on the psychosocial development and mental health of youth Brazili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 23 publications
(45 reference statements)
0
6
0
4
Order By: Relevance
“…Regarding the mental health of young people, studies have confirmed that the development of accepting and mutually beneficial relationships, as well as the construction of a sense of participation and contribution, have been effective in the feeling of psychological well-being when faced with difficulties, in promoting health, and in predicting mental disorders ( Fonte et al, 2017 ; Schotanus-Dijkstra et al, 2017 ; Milistetd et al, 2021 ). Longitudinal data have indicated that psychological well-being prevents the first incidence of mental disorders, as well as playing a protective role in the development of any DSM-IV disorder ( Schotanus-Dijkstra et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Regarding the mental health of young people, studies have confirmed that the development of accepting and mutually beneficial relationships, as well as the construction of a sense of participation and contribution, have been effective in the feeling of psychological well-being when faced with difficulties, in promoting health, and in predicting mental disorders ( Fonte et al, 2017 ; Schotanus-Dijkstra et al, 2017 ; Milistetd et al, 2021 ). Longitudinal data have indicated that psychological well-being prevents the first incidence of mental disorders, as well as playing a protective role in the development of any DSM-IV disorder ( Schotanus-Dijkstra et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Longitudinal data have indicated that psychological well-being prevents the first incidence of mental disorders, as well as playing a protective role in the development of any DSM-IV disorder ( Schotanus-Dijkstra et al, 2017 ). Age also seems to contribute to higher levels of positive mental health, as younger individuals had higher rates of positive mental health ( Fonte et al, 2017 ; Milistetd et al, 2021 ). A hypothesis for these findings was raised by Milistetd et al (2021) , in a study with young Brazilian athletes (e.g., swimmers, judokas, tennis players, basketball players, etc.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations